A novel automated lumen segmentation and classification algorithm for detection of irregular protrusion after stents deployment. Issue 1 (13th November 2019) - Yang, Su; Yoon, Hyuck‐Jun; Yazdi, Seyed Jamaleddin Mostafavi; Lee, Jong‐Ha
Abstract: Background: Clinically, irregular protrusions and blockages after stent deployment can lead to significant adverse outcomes such as thrombotic reocclusion or restenosis. In this study, we propose a novel fully automated method for irregular lumen segmentation and normal/abnormal lumen classification. Methods: The proposed method consists of a lumen segmentation, feature extraction, and lumen classification. In total, 92 features were extracted to classify normal/abnormal lumen. The lumen classification method is a combination of supervised learning algorithm and feature selection that is a partition‐membership filter method. Results: As the results, our proposed lumen segmentation method obtained the average of dice similarity coefficient (DSC) and the accuracy of proposed features and the random forest (RF) for normal/abnormal lumen classification as 97.6% and 98.2%, respectively. Conclusions: Therefore, we can lead to better understanding of the overall vascular status and help to determine cardiovascular diagnosis.